Prescribed psychotropic medication patterns among treated Foster Care enrollees: a single institution study - Cosme, Celica Glenn; Rudig, Nathan O.; Borsellino, Philip J.; Chea, Deanna; Krider, Reese I.; Durette, Lisa (Frontiers in Psychiatry, 2024)
Background While several state-based studies have shown that children in foster care are more likely to be prescribed psychotropic medications and experience concomitant medication use both within and among medication class, these patterns have not been explored in the state of Nevada, which lacks state mandated oversight of psychotropic prescribing for foster care enrolled youth. Methods Data from an electronic medical record system from a single institution were analyzed to examine the prevalence of psychotropic prescribing and concomitant medication use in children ages 2 to 19 who were enrolled and received psychotropic prescriptions between July 2019 to June 2022. Results Out of 569 distinct psychotropic medication treatment episodes within this cohort, the most frequent psychotropic classes prescribed were non-stimulant ADHD medications (alpha-agonists and atomoxetine, 31.5%), atypical antipsychotics (22.1%), antidepressants (20.6%), and stimulants (16.0%). The use of stimulants and non-stimulant ADHD medications decreased in older age groups while the use of antidepressants and antipsychotics increased in older age groups. During the three-year period studied, 24.0% of psychotropic medications prescriptions increased in dosage. Treatments were prescribed for only one month in 43.8% of youth. In children prescribed psychotropic medications, concomitant medication use for at least 60 days occurred in 28.0% of children who had any psychotropic medication prescribed. Conclusion Within the cohort of 273 foster care enrolled subjects aged 2 to 19 years old who received psychotropic medication prescriptions, non-stimulant ADHD medications (both alpha-agonists and atomoxetine) and atypical antipsychotics were more commonly co-prescribed additional psychotropic medication compared to other co-prescribed medication categories. This study illustrates prescribing patterns in a community mental health clinic focused on judicious prescribing of psychotropic medications in foster care enrolled youth. Despite this, 41% of the youth treated in this clinic received at least one prescription for psychotropic medication, and of those, 27.8% were prescribed more than one psychotropic medication at the same time. More studies are necessary to understand the underlying causes of high prevalence of concomitant medication use and prescribing practices of psychotropic medications use in foster care involved pediatric populations.